2011
DOI: 10.1159/000326082
|View full text |Cite
|
Sign up to set email alerts
|

Tetramethylpyrazine Inhibits Hypoxia-Induced Pulmonary Vascular Leakage in Rats via the ROS-HIF-VEGF Pathway

Abstract: Tetramethylpyrazine (TMP) is a reactive oxygen species (ROS) antagonist that has potent properties for the treatment of a variety of vascular diseases, such as ischemic stroke and pulmonary hypertension secondary to chronic obstructive pulmonary diseases. However, there are few data about the role of TMP in hypoxia-induced pulmonary vascular leakage. This study examined the effect of TMP on hypoxia-induced pulmonary vascular leakage and the underlying mechanisms. Rat pulmonary microvascular endothelial cells (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…An earlier report showed that thymosin beta-4-induced HIF-1α stabilization in human cervical tumor cells is ROS-dependent [53]. However, the mechanism whereby ROS influences HIF-1α expression has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier report showed that thymosin beta-4-induced HIF-1α stabilization in human cervical tumor cells is ROS-dependent [53]. However, the mechanism whereby ROS influences HIF-1α expression has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…TMP also decreased the expression of intracellular adhesion molecule-1 and heat shock protein 60, suggesting its anti-inflammatory role in endothelial cells (9). As a reactive oxygen species antagonist, TMP protected the rat pulmonary microvascular endothelial cells from hypoxia and TMP-treated animals demonstrated less pulmonary vascular leakage compared with those exposed to hypoxia alone (10). It was also reported that TMP, or its derivatives, suppressed the apoptosis of HUVECs induced by hydrogen peroxide (11).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and laboratory studies on herbal medicine draw special attention to ROS-pathway-mediated injury in CVDs [ 19 ]. The scavenging ROS function of TMP on hypoxia induced pulmonary vascular leakage had been explored [ 20 ], and H 2 O 2 -induced human umbilical vein endothelial cells (HUVECs) were also employed to evaluate protective effect of TMP on oxidative stress, as well as its antiapoptotic properties [ 21 ]. By testing its effect on C2C12 myotube, Gao and his coworkers [ 22 ] reported that TMP could restrain mitochondrial ROS generation and upregulate the expression of PGC1, NRF1, and Tfam, which reflects mitochondrial biogenesis.…”
Section: Medicinal Use Of Tmpmentioning
confidence: 99%